(untitled) (Global Journal of Management and Business Research, 2021)
The purpose of this study was to investigate the effect of microfinance loan on poverty reduction in Rwanda. The study sought to identify the achievements of microfinance loans to the individuals, explore the perceptions of microfinance beneficiaries on poverty reduction and determine the effect of microfinance loans on the economic growth. The target population for this study was 6228 persons, which included employees and clients of COPEDU PLC, Remera Branch. The study adopted descriptive research design to collect data from the selected sample size. The primary data was collected using questionnaires that were randomly distributed to the sample population. The data collected was analyzed using the Statistical Package for Social Sciences (SPSS) software to determine the mean, mode, standard deviation and inferential statistics related to the study. The findings from the study indicate that microfinance loans have a significant effect on poverty reduction. The study found that microfinance loans empower the poor and enable them to overcome the challenges that they face. The provision of microfinance loans has led to start-ups, growth and expansion of micro and small businesses resulting in asset building, job creation, poverty reduction and improved standard of living.